Creep Behaviour in Cracked Sections of Fibre Reinforced Concrete Proceedings of the International RILEM Workshop FRC-CREEP 2016 - Serna, Pedro; Llano-Torre, Aitor; Cavalaro, Sergio H. P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2017)
This is the first publication ever focusing strictly on the creep behaviour in cracked sections of Fibre Reinforced Concrete (FRC). These proceedings contain the latest scientific papers about new testing methodologies, results and conclusions of multiple experimental campaigns and recommendations about significant factors of long-term behaviour, experiences from more than ten years of creep testing and some reflections about future perspectives on this topic. This book is an essential reference for all researchers of creep behaviour on FRC. This volume is the result of the efforts of the RILEM TC 261-CCF, that has been working since 2014 to develop standardized methodologies and guidelines to compare results from different laboratories and get a better understanding of the significant parameters related to creep of FRC.
Keynote Lectures -- Factors influencing creep of cracked fibre reinforced concrete: What we think, we know & what we do not know, by R. Gettu, R. Zerbino and S. Jose -- Creep testing methodologies and results interpretation, by N. Buratti and C. Mazzotti -- Session 1: Influence of fibre type on creep -- Flexural creep tests on beams - 8 years of experience with steel and synthetic fibres, by W. Kusterle -- Experiences from 14 years of creep testing of steel and polymer fibre reinforced concrete, by S. Van Bergen, S. Pouillon and G. Vitt -- Creep deformations of structural polymeric macrofibers, by R. Vrijdaghs, M. di Prisco and L. Vandewalle -- Tensile creep of cracked steel fibre reinforced concrete: Mechanisms on the single fibre and at the macro level, by W.P. Boshoff and P.D. Nieuwoudt -- Flexural post-cracking creep behaviour of macro-synthetic and steel fiber reinforced concrete, by P. Pujadas, A. Blanco, S.H.P. Cavalaro, A. de la Fuente and A. Aguado -- Session 2: Creep on special materials -- Behavior of cracked cross-section of fibre reinforced UHPFRC under sustained load, by D. Casucci, C. Thiele and J. Schnell -- Experimental study on time-dependent behavior of cracked UHP-FRCC under sustained loads, by T. Nishiwaki, S. Kwon, H. Otaki, G. Igarashi, F.U.A. Shaikh and A. P. Fantilli -- Creep behaviour of cracked high performance fibre reinforced concrete beams under flexural load, by E. Galeote, A. Blanco, A. de la Fuente and S.H.P. Cavalaro -- Time-dependent flexural behaviour of SFRSCC elements, by V.M.C.F. Cunha, J.A.O. Barros and Amin Abrishambaf -- Session 3: Creep testing methods -- Effect of residual strength parameters on FRC flexural creep: Multivariate analysis, by E. García-Taengua, A. Llano-Torre, J.R. Martí-Vargas and P. Serna -- Mid-term behaviour of fibre reinforced sprayed concrete submitted to flexural loading, by C. Larive, D. Rogat, D. Chamoley, A. Regnard, T. Pannetier and C. Thuaud -- Effect of beam width on the creep behaviour of cracked fibre reinforced concrete, by R. Zerbino, G.M. Giaccio, D.H. Monetti and M.C. Torrijos -- Macro-synthetic fibre reinforced concrete: Creep and creep mechanisms, by A.J. Babafemi and W.P. Boshoff -- Session 4: Influence of applied load on creep tests -- Influence of fibre reinforcement on the long-term behaviour of cracked concrete, by A. Llano-Torre, S.E. Arango, E. García-Taengua, J.R. Martí-Vargas and P. Serna -- Creeping effect of SFRC elements under specific type of long term loading, by D. Nakov, G. Markovski, T. Arangjelovski and P. Mark -- Creep behavior of a SFRC under service and ultimate bending loads, by D. Daviau-Desnoyers, J.-P. Charron, B. Massicotte, P. Rossi and J.-L. Tailhan -- Durability of FRC beams exposed for long-term under sustained service loading, by L. Candido, F. Micelli, E. Vasanelli, M.A. Aiello and G. Plizzari.
Keywords: Building materials; Materials -- Analysis; Building Materials; Characterization and Analytical Technique; Structural Materials